Thoracoscopic removal of ectopic mediastinal parathyroid adenoma causing hyperparathyroidism: a rare entity - Ezel Erşen; Burcu Kılıç (Videosurgery and Other Miniinvasive Techniques)
Ectopic mediastinal parathyroid adenomas are uncommon. Here, we report the successful thoracoscopic removal of a mediastinal parathyroid adenoma from a patient with hypercalcemia. A 58-year-old female patient was referred to our department with persistent hypercalcemia. Serum calcium and phosphorus levels were 13.2 mg/dl and 2.5 mg/dl respectively, while the intact parathormone level was 798.9 pg/ml. Parathyroid computed tomography revealed a solid and well-defined mass at the anterior mediastinum close to the distal aorta. Once the contrast was enhanced, our pre-diagnosis was ectopic parathyroid adenoma. The mass was detected at the anterior mediastinum, dissected free from the surrounding tissue and excised. The capsulated mass, which had a diameter of 3 × 1.5 × 0.7 cm, was confirmed as parathyroid adenoma histopathologically. Postoperative calcium and parathormone levels decreased dramatically to normal levels. Anterior mediastinal localization of an ectopic parathyroid adenoma is a rare entity. The transsternal approach is the most preferred method, but video-thoracoscopy can be used safely and effectively.